دور العلامة التجارية في الترويج لمنتوج المؤسسة دراسة ميدانية مؤسسة بيع السيارات رونو سوق اهراس - محرقي صفاء (My University, 2014)
Study Summary Brands are considered the visual identity of an organization. For example, the Dior brand gives the organization its identity based on offering elegance and perfection to the modern, liberated woman. This makes all brands carry certain promises and benefits offered to their customers or audiences. Our study was not isolated from the influence and contribution of these brands on audience choices. Our study, entitled: The Role of Branding in Promoting the Company's Product, was based on the question: To what extent does the brand contribute to promoting the company's product? The organization that served as the subject of the study was the Renault car dealership in Souk Ahras. We first covered the theoretical context, which included two chapters. The first contained information about trademarks, their types, forms, and conditions. The second chapter also covered promotion, its types and methods, as well as its objectives. We then headed out into the field with a clear idea of ​​what we wanted to research. By practicing non-participant observation, we were able to observe some of the interactions between the organization's employees and their customers, within the limits of what time and circumstances allowed. Shortly thereafter, we conducted a series of interviews with the five sample members, selected for being permanent employees. The questions varied in order to obtain information during the exploratory phase. After designing the questionnaire and presenting it to a group of professors for review, we modified it, took it to the field, and distributed it to our sample—that is, to every customer or client we encountered within the organization. They were required to be familiar with the organization's promotional communications efforts, including those aimed at engaging with its diverse audiences within its environment. ------------------------------ ملخص الدراسة تُعتبر العلامات التجارية بمثابة الهوية البصرية لأي مؤسسة. على سبيل المثال، تُضفي علامة ديور التجارية على المؤسسة هويتها القائمة على تقديم الأناقة والكمال للمرأة العصرية المتحررة. وهذا ما يجعل جميع العلامات التجارية تحمل وعودًا ومزايا معينة تُقدمها لعملائها أو جمهورها. لم تكن دراستنا بمعزل عن تأثير هذه العلامات التجارية ومساهمتها في اختيار الجمهور. استندت دراستنا، المعنونة: دور العلامة التجارية في الترويج لمنتجات الشركة، إلى السؤال التالي: إلى أي مدى تُساهم العلامة التجارية في الترويج لمنتجات الشركة؟ كانت وكالة رينو للسيارات في سوق أهراس موضوع الدراسة. تناولنا في البداية السياق النظري، والذي تضمن فصلين. تضمن الفصل الأول معلومات حول العلامات التجارية وأنواعها وأشكالها وشروطها. كما تناول الفصل الثاني الترويج وأنواعه وأساليبه وأهدافه. ثم انطلقنا إلى الميدان بفكرة واضحة عما نريد بحثه. من خلال ممارسة الملاحظة غير التشاركية، تمكنّا من رصد بعض التفاعلات بين موظفي المؤسسة وعملائهم، ضمن حدود الوقت والظروف المتاحة. بعد ذلك بوقت قصير، أجرينا سلسلة من المقابلات مع أعضاء العينة الخمسة، الذين تم اختيارهم كموظفين دائمين. تنوعت الأسئلة للحصول على معلومات خلال مرحلة الاستكشاف. بعد تصميم الاستبيان وعرضه على مجموعة من الأساتذة للمراجعة، قمنا بتعديله، ونقله إلى الميدان، وتوزيعه على عينة البحث - أي على كل عميل أو متعامل قابلناه داخل المؤسسة. طُلب منهم الإلمام بجهود المؤسسة في مجال الاتصالات الترويجية، بما في ذلك تلك التي تهدف إلى التواصل مع جماهيرها المتنوعة في بيئتها.
Keywords: العلامة التجارية، الترويج، منتوج، المؤسسة